METHODS OF USING UAVS DURING AVIATION SEARCH AND RESCUE - Leshchenko, Gennady; Mandryk, Yana; Stratonov, Vadym; Davydov, Serhiy (Science-based technologies, 2021)
During the last decade, the use of unmanned aerial vehicles has reached large scale. UAVs are used in various spheres of human life (from military to agricultural) and the areas of involvement of UAVs are constantly expanding, thereby meeting the needs of consumers. The field of aviation search and rescue support of flights is not an exception. This need was primarily due to economic factors and the need to increase the efficiency of search and rescue operations. In this review article, the authors analyze the main ways to use UAVs during aviation search and rescue. The relevance of the study is confirmed by real cases of UAV use in emergencies. In particular, the effectiveness of such use was confirmed during the floods in the Balkans, when the involvement of UAVs managed to avoid the mine danger caused by landslides. Another case that successfully illustrates the relevance of the study took place during the aftermath of the earthquake in the Chinese province of Yunnan. Due to the high efficiency of UAVs, we conducted research on the types of UAVs used by the SES of Ukraine. Research has also been conducted on the main tasks that UAVs solve. In the course of the research we noted that the introduction of UAVs in the field of civil defense of Ukraine is in the initial phase, namely at the stage of formation of the legal framework, and their involvement in search operations is not a common practice. At the same time, analyzing the list of tasks, we note their wide range, covering most of the possible components of air reconnaissance: monitoring, reconnaissance, support of search and rescue operations, possibility of delivery special cargo or medicines to dangerous areas, etc. Along with the tasks solved by UAVs, the article provides related data of visual detection range of search objects in normal conditions, at night and at low altitudes. The article also analyzes the basic schemes of search for emergency objects and victims ("Comb", "Parallel search lines", "Expanding Square" and "Specific route") with their general overview. Summing up the study, the authors conclude that it is important to train UAV operators, which must have the professional standard, because only in combination with a "modern UAV-professional operator" can achieve maximum efficiency